EFFECT OF DIALYZER REUSE UPON UREA REDUCTION RATIO (URR), KT/V UREA AND SERUM ALBUMIN IN REGULAR HEMODIALYSIS PATIENT - Ni Made Amelia R. Dewi; Budi Suprapti; I Gde Raka Widiana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Reuse of dialyzers for hemodialysis can help in bringing down the cost of hemodialysis. On the other hand reuse of dialyzer may change dialyzer integrity. This study was undertaken to determine dialyzer reuse effect on Urea Reduction Ratio (URR), Kt/V urea and serum albumin. This was prospective study in Sanglah Public General Hospital Denpasar. Inclusion criteria for this study were patients who receive hemodialysis more than 3 months on twice weekly hemodialysis. In the study we used hollow fiber or dialyzer Elisio type H-130H reprocessed with Renaline automatically by machine renatron. After each session blood urea, post dialysis weight and serum albumin were measured. Measurements was performed on the use new dialyzer, 1st reuse, 4th reuse and 7th reuse. The dialyzer was discarded, if TCV fell below 80% of baseline value. Kt/V and urea reduction ratio (URR) were calculated as measure of dialysis adequacy. A total of 23 people completed the study. There was a lack of uniformity duration of hemodialysis, so that we also performed an analysis using a uniform length hemodialysis duration (4.5 hours) with 15 samples. There were no significant difference between URR and Kt/V urea of new dialyzer and dialyzer reprocessed by renaline respectfully with p=0.131 and p=0.373. If we analyzed only using uniform time of dialysis (4.5 h) the value of URR and Kt/V urea between new and reused dialyzer not significantly different with p=0.520 and p=0.784. There was also not found significant differences between serum albumin of the use new dialyzer and reused dialyzer by the time of uniform or non-uniform, respectfully with p=0.271 and 0.073. Reuse dialyzer does not alter efficacy of hemodialysis.Key words : Dialyzer, Urea Reduction Ratio (URR), Kt/V Urea, Albumin, Total Cell Volume (TCV)